AKIBAT HUKUM TERHADAP PERJANJIAN HUTANG-PIUTANG YANG DIBUAT OLEH NOTARIS DENGAN JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN - Ganitra Dhiksa Weda, I Wayan; Putri ME, Purwani, Sagung (Kertha Semaya : Journal Ilmu Hukum, 2014)
This paper shall be emtitled as Consequences of the Law Against Debt-Receivable Agreement Made By Notary With Fiduciary Guarantee Not Registered, who in his writings uses normative legal research methods for examining the fundamentals of law and law sistimatika, and implementations. Liquidator agreement made by the notary by using fiduciary assurance that is not registered is very difficult to solve when the debtor defaulting. Therefore, this article will explain what was the law of fiduciary assurance is not registered and will explain about how efforts to guarantee defaulting fiduciary solutions are not registered and transferred to another party.
Keywords: Agreements, The Lending, Fiduciary, Legal Consequences